Disseminação de conteúdo audiovisual e instrucional como estratégia de formação de identidade e expansão das fintechs brasileiras - Pinto, Kleber Alves (2020)
This study aims to discuss the use of instructional audiovisual content, its distribution and promotion on digital platforms as a communication strategy within the fintech environment. It is limited to the area of Communication Sciences, subareas Digital Communication and Marketing. Through a theoretical framework on connected contemporary society, the technologies available to marketing and the Brazilian entrepreneurship scenario of startups, we seek to understand how the instructional audiovisual content collaborates in the strategy of identity formation and expansion of fintechs; and an analysis of the communication channels of financial technology companies on the YouTube platform through the disseminated content is proposed